GPS rates of vertical bedrock motion suggest late Holocene ice-sheet readvance in a critical sector of East Antarctica - Matt King; Christopher Watson; White, D (2022)
We investigate present-day bedrock vertical motion using new GPS timeseries from the Totten-Denman glacier region of East Antarctica (∼77-120°E) where models of glacial isostatic adjustment (GIA) disagree, glaciers are likely losing mass, and few data constraints on GIA exist. We show that varying surface mass balance loading (SMBL) is a dominant signal, contributing random-walk-like noise to GPS timeseries across Antarctica. In the study region, it induces site velocity biases of up to ∼+1 mm/yr over 2010-2020. After correcting for SMBL displacement and GPS common mode error, subsidence is evident at all sites aside from the Totten Glacier region where uplift is ∼1.5 mm/yr. Uplift near the Totten Glacier is consistent with late Holocene ice retreat while the widespread subsidence further west suggests possible late Holocene readvance of the region’s ice sheet, in broad agreement with limited glacial geological data and highlighting the need for sampling beneath the current ice sheet.